Respuesta :
We are required to find the solutions given by the following system of equations;
3x+y=1
5x+y=3
subtracting the top equation form the bottom equation we get:
2x=2
dividing both sides by 2 we get
x=1
thus substituting the value of x in the above equation we get:
3(1)+y=1
3+y=1
thus;
y=1-3
y=-2
the answer is:(1,-2)
3x+y=1
5x+y=3
subtracting the top equation form the bottom equation we get:
2x=2
dividing both sides by 2 we get
x=1
thus substituting the value of x in the above equation we get:
3(1)+y=1
3+y=1
thus;
y=1-3
y=-2
the answer is:(1,-2)